Implications of the distinct or interchangeable use of the terms “ESG” and “sustainability” on reporting by global banks in the context of COVID-19 - Masemola, Mokganye Mathabo (College of Accounting, 2025)
The use of the buzzwords “ESG” and “sustainability” has been on the rise. Although used interchangeably, the terms “ESG” and “sustainability” have different meanings. This study explored the differences and similarities between the ESG disclosures and sustainability disclosures of banks, including whether there is an acknowledgement of the difference between the terms “ESG” and “sustainability” in 2019 and 2021 and the implications regarding reporting practices. The integrated reports and sustainability reports analysed are for a sample of 25 banks, as banks have a dual responsibility in terms of ESG and sustainability reporting. The sampled banks are from South Africa, Japan, the United Kingdom, the United States and France - where integrated reporting and sustainability reporting exist. An interpretative content analysis was performed on the reports, with results being recorded in a template. The implication of the distinction or non-distinction was further investigated in terms of the number of reports used to report on the matters, the purpose of the report, the target audience for each report, what constitutes the definition of materiality in the context of each report and whether Covid-19 contributed towards a change in the materiality constitution of those reports between 2019 and 2021. The results show that banks do not distinguish between “ESG” and “sustainability”. Further, the findings suggest that the non-distinction between the two terms by authoritative guidance, frameworks and standards mandatorily adopted results in no separation between the forms of reporting used to report on ESG matters and sustainability matters. As a result, more than one report is used to report on ESG matters and sustainability matters. However, the ESG matters and sustainability matters are disclosed together, leading to the purpose, target audience and materiality definitions being the same for both ESG matters and sustainability matters. Covid-19 is not listed as a critical contributor to determining material matters in 2021 as opposed to 2019.